Assessment of spectrum-matched time histories for floor response spectra generation. (April 2022) - Li, Bo; Zhou, Yang
Abstract: The floor response spectra (FRS) are usually determined by time history analyses using spectrum-matched time histories. However, previous studies reported that spectrum-matched time histories may cause a biased estimate of FRS, which raises a challenge of FRS generation for nuclear power plant structures. The study focuses on resolving the challenge. We begin the study by discussing characteristics of amplitude-scaled and spectrum-matched ground motions for seismic design and analysis of nuclear facilities. Then, we explore the influence of spectral matching on the change of ground motion parameters. Using suites of amplitude-scaled and spectrum-matched ground motions, we determine FRS for examples of typical structures, and investigate how the change of ground motion parameters due to spectral matching affects the biased estimate of FRS. The investigation shows that, the change of damping scaling factor is remarkably correlated with the biased estimate of FRS. Thus, we propose the improved spectrum-matched time histories for floor response spectra generation. Taken a service building of nuclear power plants as an example, the study shows that, the improved spectrum-matched are adequate to achieve approximate unbiased estimate of FRS under different damping values.